Là où ça sent la merde / ça sent l’être. Semiotic Considerations on Poop Cafés in South Korea - Baron, Giustina Benedetta (E|C, 2025)
This semiotic research explores the emergence of “weird food” within South Korea’s burgeoning coffee culture, particularly through themed cafés that challenge conventional dining norms. Notably, the Poop Café (Ddong Café) serves as a case study, exemplifying the transformation of a traditionally taboo subject – feces – into a playful and consumer-friendly motif. This study examines how the café’s whimsical presentation of food and beverages, including toilet-shaped mugs and aesthetically styled dishes resembling excrement, re-contextualizes cultural associations of feces with fortune and cuteness. By analyzing the semiotic implications of these unusual theme, this research highlights the ways in which poop cafés engage visitors in a sensory experience that transcends mere consumption, inviting them to partake in a complex interplay of cuteness, disgust, and archaic superstitions. Through this lens, the phenomenon of weird food emerges as a reflection of contemporary post-medial conviviality, offering insights into the evolving landscape of culinary identity in South Korea.